Influence of Bypass Fat and Mineral Supplementation during Transitional Period on Plasma Trace Minerals Profile and Postpartum Fertility in Jafarabadi Buffaloes - Vala, KB; Dhami, AJ; Kavani, FS; Ramani, VP; Parmar, SC (Indian Journal of Veterinary Sciences and Biotechnology, 2019)
This investigation was carried out on 40 advanced pregnant Jafarabadi buffaloes of 2–4 parity equally divided into two groups, viz., controland treatment groups. The control animals were maintained on standard routine farm feeding, and the animals of the treatment groupreceived additional oral supplements of 50 g chelated mineral mixture and 150 g bypass fat daily along with concentrates for 6 weeksprepartum and 8 weeks postpartum. The bypass fat was given @ 15 g/liter of milk produced limiting up to 200 g/head/day from 15–60days postpartum. Ten animals in each control and treatment group further received Inj. Stimvet 5 mL (micro-minerals) around day 45prepartum and on day of calving. Half of these Stimvet treated and control subgroups also received ecbolic Exapar (n = 5) 2 boli/day for4 consecutive days postpartum. Blood samples were obtained from all animals by jugular vein puncture on the day –45, –30, –7 and 0(day of calving), 7, 15, 30, 45, 60 peripartum for estimation of plasma trace minerals, viz., zinc, iron, copper, cobalt, and manganese. Theplasma zinc and copper concentrations were found to be higher on day 30 prepartum and again on day 7 postpartum in Stimvet injectedgroups.Moreover, the overall pooled mean concentration of zinc was significantly higher in nutrients supplemented than the controlgroup. The plasma concentrations of iron, cobalt, and manganese did not reveal any specific trend or significant variations betweengroups or between periods within any of the groups. Further, the peripartum oral nutrients supplementation significantly shortenedthe periods of placental expulsion time and uterine involution, with early onset of postpartum first estrus, apparently shorter serviceperiod and enhanced pregnancy rate in comparison to control group. The influence of Stimvet and Exapar alone or in combination,however, did not show a significant beneficial effect on these traits, except shortened placental expulsion time and higher plasma zincand cobalt status. Hence, the Jafarabadi buffalo keepers may be advised to provide additional oral nutrients supplementation in the formof bypass fat and chelated minerals over routine feeding to their animals during a transitional period for improved postpartum fertility